Considering Restorative Justice and Peacebuilding: A Challenge for Ahmadiyya Communities in Indonesia - Mochamad Sodik; B.J. Sujibto; Gufron Gufron (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
Having endured a history of persecution, violent attacks, and discrimination, from civil rights violations to expulsions, the Ahmadiyya community in Indonesia has pursued various strategies to promote peace and harmony. Using the Ahmadiyya settlement in Manislor, Kuningan, as a case study, this article examines how restorative justice might support peacebuilding between Ahmadiyya adherents and their offenders. We ask two questions: To what degree can restorative justice contribute to peacebuilding, and what factors either aid or hinder its practice in Manislor? Through a qualitative case study approach that combines observation, focus groups, interviews, and archival research, we identify restorative justice elements that reinforce peacebuilding efforts already initiated by Ahmadiyya leaders and the community. These elements include active dialogue and cultural bridge-building through visits to religious figures and local stakeholders, as well as expanded social engagement and charitable activities already underway in Manislor. This article develops a theoretical framework connecting restorative justice to peacebuilding in a context previously unexamined in the literature, and it provides a practical example that may inform restorative practices elsewhere, especially among other Ahmadiyya communities in Indonesia.